Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00213-017-4655-0
|View full text |Cite
|
Sign up to set email alerts
|

Habitual nicotine-seeking in rats following limited training

Abstract: Operant responding for IV nicotine may rapidly come under habitual control, potentially contributing to the tenacity of tobacco use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
0
14
0
1
Order By: Relevance
“…If they do not show a devaluation effect, the response is deemed habitual in being controlled directly by an S−R association. Four versions of this method have been used to test whether drugs promote habitual behaviour, as outlined in the text [30,[174][175][176]. The outcome-devaluation task in humans: Typically, participants learn that two responses (R1 and R2) earn different rewarding outcomes (O1 and O2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If they do not show a devaluation effect, the response is deemed habitual in being controlled directly by an S−R association. Four versions of this method have been used to test whether drugs promote habitual behaviour, as outlined in the text [30,[174][175][176]. The outcome-devaluation task in humans: Typically, participants learn that two responses (R1 and R2) earn different rewarding outcomes (O1 and O2).…”
Section: Methodsmentioning
confidence: 99%
“…The second criticism is that habitual control is fragile because sensitivity to devaluation is immediately restored in reacquisition tests where drug seeking produces the devalued reinforcer. This restoration of sensitivity to devaluation in reacquisition tests is found for both drug seeking [30,[174][175][176] and food seeking in chronically drug-exposed animals [180,181]. If one accepts that in human drug users' natural environment, extinction conditions rarely occur, but conditions comparable to reacquisition prevail (i.e.…”
Section: Studies With Laboratory Animalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Drug addicts are impaired on gambling and reversal learning tasks [4][5][6] , and their behaviors are biased toward habitual (as opposed to goal-directed) control [7][8][9][10] . In rodent models, cocaine exposure or selfadministration results in cognitive inflexibility in reversal learning tasks 11,12 and exposure to various drugs of abuse, including cocaine 13,14 , ethanol [15][16][17] , methamphetamine 18,19 , and nicotine 20,21 promotes the formation of habits, as evidenced by response insensitivity to outcome devaluation and/or contingency degradation. Finally, several studies have demonstrated persistent drug seeking despite punishment in rodents 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, animals are given the opportunity to perform the instrumental response for the devalued outcome in an extinction test. Four studies using this design have found that the drug-seeking response is not reduced by the devaluation treatment in the extinction test (Dickinson et al, 2002;Miles et al, 2003;Mangieri et al, 2012;Loughlin et al, 2017). Such insensitivity to devaluation suggests that the drug-seeking response is not goal-directed (not controlled by knowledge of the current value of the outcome) but rather, is habitual, that is, elicited automatically by the stimulus context.…”
Section: Introductionmentioning
confidence: 99%